ADMINISTRATIVE AND LEGAL ASPECTS PROTECTION OF DEFENSE OF UKRAINE - Галунько, Валентин Васильович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Review of the monograph V.Y. Pashynsky "Providing Defense of Ukraine: Administrative and Legal Aspects". It is noted that the relevance of the monograph is due to the public need for an objective and comprehensive study, scientific research of the theoretical and practical issues of the administrative and legal support of the defense of Ukraine in the conditions of the special period, the legal regime of the military state, during the operation of the united forces for the liberation of the temporarily occupied territory our state. This monograph is a fundamental scientific work, is the first comprehensive legal study of problem issues in the administrative and legal defense of Ukraine, which considers the importance and role of legal science and administrative law for the defense of Ukraine.